Fluorescence Probe for Imaging N-Methyl- d -aspartate Receptors and Monitoring GSH Selectively Using Two-Photon Microscopy - Kwon, Nahyun; Lim, Chang Su; Ko, Gyeongju; Ha, Jeongsun; Lee, Dayoung; Yin, Jun; Kim, Hwan Myung; Yoon, Juyoung (Analytical Chemistry, 2021)
N-Methyl-d-aspartate (NMDA) is an excitotoxic amino acid used to identify a specific subset of glutamate receptors. The activity of NMDA receptors is closely related to the redox level of the biological system. Glutathione (GSH) as an antioxidant plays a key role with regard to modulation of the redox environment. In this work we designed and developed a GSH-specific fluorescent probe with the capability of targeting NMDA receptors, which was composed of a two-photon naphthalimide fluorophore, a GSH-reactive group sulfonamide, and an ifenprodil targeting group for the NMDA receptor. This probe exhibited high selectivity toward GSH in comparison to other similar amino acids. Two-photon fluorescence microscopy allowed this probe to successfully monitor GSH in neuronal cells and hippocampal tissues with an excitation at 750 nm. It could serve as a potential practical imaging tool to explore the function of GSH and related biological processes in the brain.
Keywords: Biological process; Fluorescence probes; Fluorescent probes; Glutamate receptor; N methyl D aspartate receptor; N-methyl-d-aspartate; Two photon microscopy; Two-photon fluorescence microscopy